Evidence for Vertical Transmission of HPV from Mothers to Infants. (1st March 2010) - Smith, Elaine M.; Parker, Michael A.; Rubenstein, Linda M.; Haugen, Thomas H.; Hamsikova, Eva; Turek, Lubomir P.
Abstract : Few large studies have evaluated concordance based on a broad spectrum of human papillomavirus (HPV) types in oral and genital specimens of mothers and their recently born infants. This information is important in determining whether HPV vaccines administered prior to pregnancy may be useful for preventing vertical transmission. HPV DNA was positive in 30% of mothers and 1.5% of newborns. Maternal/newborn concordance (HPV+/+ or HPV− / − ) was 71%. Among HPV DNA+ mothers, only 3% of their infants were DNA+ and only 1 pair had the same HPV type. Among HPV− women, 0.8% of infants were HPV+. HPV DNA detected in hospitalized newborns reflects current infection transmitted to infants during pregnancy or delivery. None of the mother/baby HPV DNA+ concordance pairs detected viral types found in HPV vaccines suggesting that vaccination prior to pregnancy is unlikely to be efficacious in preventing vertical transmission.